A gypsum coating that can utilize solid waste and is not easy to fall off and a preparation method thereof

By using lithium slag powder to replace traditional filler powder, and by mixing titanium dioxide and multiple whiteness lithium slag powders, the problem of filling powder consumption in gypsum coatings is solved, and waste utilization and coating adhesion are improved.

CN117050561BActive Publication Date: 2025-04-11SHANGHAI CIVIL ENG GRP CO LTD OF CREC +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310914388.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-04-11
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

Filler powder in gypsum coatings requires the mining of natural minerals, which is costly and consumes natural resources.

Method used

Lithium slag powder is used to replace traditional filler powder, and by adding titanium dioxide or lithium slag powder with multiple whitenesses, the whiteness of the filler powder is ensured to be uniform, and the problem of color fluctuations in lithium slag powder is solved.

Benefits of technology

Waste utilization is achieved, consumption of natural resources is reduced, and the adhesion and color uniformity of gypsum paint are improved, making it less likely to fall off.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of coating compositions based on inorganic substances, and discloses a gypsum coating that can utilize solid waste and is not easy to fall off and a preparation method thereof, wherein the dry powder of the gypsum coating comprises the following components in parts by mass: 30-70 parts of gypsum powder; 30-70 parts of filler powder; the filler powder is lithium slag powder whose whiteness is improved by adding titanium dioxide or lithium slag powder with higher whiteness, and the filler powder whiteness is not less than 55%; 0.4-1 parts of hydrophilic fiber powder. In the present invention, lithium slag powder is used to replace talcum powder / light calcium powder, which not only realizes waste utilization and reduces the consumption of natural resources, but also improves the adhesion of the coating, making it not easy to fall off and reducing the processing requirements for the building base; in the present invention, by using titanium dioxide and a variety of whiteness lithium slag powder mixed mode, it is ensured that the color of the lithium slag powder is uniform and the whiteness meets the construction requirements, so that the color of the gypsum coating is uniform and the problem of yellowing of the lithium slag powder is overcome, and the use scene is limited after the lithium slag powder is mixed into the gypsum coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating compositions based on inorganic substances, and in particular to a gypsum coating which can utilize solid waste and is not easy to fall off, and a preparation method thereof. Background Art

[0002] Gypsum paint is a very commonly used paint in the construction process. It is generally used as a base coat to fill pits on the building surface and to facilitate the subsequent application of paint. Sometimes, gypsum paint is also used as a surface coat for sound absorption effects.

[0003] The two main components of gypsum paint are gypsum powder and filler powder. The gypsum powder is used to ensure the bonding strength and give the product water resistance; the filler powder is used to make the slurry of gypsum paint easier to scrape, increase smoothness and reduce costs. In addition, bentonite is generally added to gypsum paint to thicken it, fiber powder is added to resist cracking, and glue is added to increase the strength of gypsum paint after solidification.

[0004] The filler powder in gypsum paint mainly uses talcum powder, light calcium powder, or heavy calcium powder. An important requirement for filler powder is that it needs to be ground to a very fine degree to improve the smoothness of the surface after the gypsum paint is applied. Generally, its mesh size needs to be greater than 325 meshes. These filler powders need to be mined from natural minerals, and due to the large amount of gypsum paint (the thickness can reach several centimeters during spraying), the consumption of this part of natural minerals cannot be ignored.

[0005] With the booming development of the electric vehicle industry, the use of lithium-ion batteries is also increasing, which has produced a large amount of lithium slag (the material left after lithium is extracted from lithium ore). The main components of lithium slag are silicon oxide and aluminum oxide, and also contain a small amount of impurities such as calcium carbonate. In order to recycle waste, lithium slag is sometimes used to make cement.

[0006] The inventors found that lithium ore needs to be soaked and calcined repeatedly during the process of extracting lithium, so lithium slag is usually a loose porous material, which is very easy to grind and can be easily ground to 800 mesh, far exceeding the requirements of filler powder in gypsum coating, so it can be used as a filler for gypsum coating. And its microstructure is similar to fly ash, containing glass microspheres produced at high temperature, but the particle size distribution range is very wide.

[0007] However, due to the large fluctuation in the color of lithium slag, not all lithium slag is white. Many lithium slags are light yellow or grayish white. Adding them to gypsum paint will affect the appearance of the gypsum paint. Although gypsum paint is not used as a surface coating in fine decoration scenes, if this yellow / gray gypsum paint is used, the covering property requirements of the surface coating will become higher. And in those occasions where gypsum paint is directly used as a surface coating (most simple decorations directly use gypsum as a surface coating), this yellow / gray gypsum paint cannot be used at all.

[0008] Therefore, it is not possible to add lithium slag to gypsum coating at present. Summary of the invention

[0009] The invention provides a gypsum paint which can utilize solid waste and is not easy to fall off and a preparation method thereof.

[0010] The technical problem to be solved is that the filler powder in gypsum paint needs to be produced by mining natural minerals, which is costly and consumes natural resources.

[0011] In order to solve the above technical problems, the present invention adopts the following technical solution: a gypsum coating that can utilize solid waste and is not easy to fall off, wherein the dry powder of the gypsum coating contains the following components in parts by weight:

[0012] 30-70 parts of gypsum powder; gypsum powder needs to be semi-hydrated gypsum or high-temperature calcined gypsum;

[0013] 30-70 parts of filler powder; the filler powder is lithium slag powder whose whiteness is improved by adding titanium dioxide or lithium slag powder with higher whiteness, and the whiteness of the filler powder is not less than 55%;

[0014] 0.4-1 part of hydrophilic fiber powder.

[0015] Furthermore, the gypsum coating is a surface coating, and the dry powder of the gypsum coating contains the following components in parts by weight:

[0016] 50-70 parts of gypsum powder;

[0017] 30-50 parts of filler powder; the whiteness of the filler powder is 70-80%;

[0018] 0.4-1 part of hydrophilic fiber powder.

[0019] Furthermore, the gypsum coating is a primer, and the dry powder of the gypsum coating contains the following components in parts by weight:

[0020] 30-50 parts of gypsum powder;

[0021] 50-70 parts of filler powder; the whiteness of the filler powder is 55%-70%;

[0022] 0.4-1 part of hydrophilic fiber powder.

[0023] Furthermore, the lithium slag powder in the filler powder is obtained by grinding lithium slag produced by a calcination lithium extraction process.

[0024] Furthermore, the mesh size of the lithium slag powder in the filler powder is not less than 400 meshes, and is higher than the mesh sizes of the gypsum powder and the titanium dioxide.

[0025] Furthermore, the hydrophilic fiber powder is wood fiber powder or waste paper fiber powder, and the hydrophilic fiber powder is also doped with sodium carboxymethyl cellulose for further improving the bonding strength between the hydrophilic fiber powder and the rest of the gypsum coating, and the content of the sodium carboxymethyl cellulose in the hydrophilic fiber powder is 6%-10%wt.

[0026] A method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off is used to prepare the above-mentioned gypsum coating that can utilize solid waste and is not easy to fall off, and comprises the following steps:

[0027] Step 1: Take 100 parts by mass of lithium slag powder with a whiteness of no more than 55%, add titanium dioxide in portions by mass, flatten and compact the lithium slag powder and measure the whiteness of the lithium slag powder once after adding 1 part by mass of titanium dioxide and mixing, until the whiteness of the lithium slag powder is higher than 80%; then draw a whiteness-titanium dioxide addition amount curve; in the whiteness-titanium dioxide addition amount curve, the ordinate is the whiteness of the lithium slag powder after adding titanium dioxide, and the abscissa is the mass fraction of titanium dioxide added;

[0028] Step 2: Stock up multiple batches of lithium slag powder in the warehouse, each batch of lithium slag powder corresponds to a color, measure the whiteness of each batch of lithium slag powder in the warehouse and record it;

[0029] Step 3: The whiteness of the filler powder required in the construction design stage is recorded as B;

[0030] If there is lithium slag powder with a whiteness greater than B in the warehouse, filler powder is prepared by mixing two types of lithium slag powder with a whiteness greater than B and less than B;

[0031] If there is no lithium slag powder with a whiteness greater than B in the warehouse, filler powder is prepared by adding titanium dioxide to lithium slag powder with a whiteness less than B;

[0032] Step 4: After mixing the gypsum powder, filler powder and hydrophilic fiber powder, add water and mix to obtain the finished gypsum paint.

[0033] Furthermore, in step 3, two lithium slag powders with whiteness greater than B and less than B are mixed to prepare filler powder in the following manner:

[0034] Select two lithium slag powders with whiteness closest to B and one greater than B and the other less than B, the whiteness of the lithium slag powder greater than B is recorded as A, and the whiteness of the lithium slag powder less than B is recorded as C, then every 100 weight parts of filler powder contains 100 (BC) / (AC) parts by weight of lithium slag powder with whiteness greater than A, and 100 (AB) / (AC) parts by weight of lithium slag powder with whiteness less than A;

[0035] Further, in step 3, titanium dioxide is added to lithium slag powder having a whiteness less than B to prepare filler powder in the following manner:

[0036] Select a lithium slag powder with the whiteness closest to B, and record its whiteness as D;

[0037] The horizontal lines with vertical coordinates B and D intersect the whiteness-titanium dioxide addition amount curve, and the horizontal coordinate difference between the two intersection points is recorded as U. Then, the required filler powder can be obtained by adding U parts by mass of titanium dioxide to every 100 parts by mass of lithium slag powder with a whiteness of D.

[0038] Furthermore, in step 2, the CMYK color of the lithium slag powder is recorded while recording the whiteness of the lithium slag powder, wherein the lithium slag powder with a warm CMYK color is recorded as warm-colored lithium slag powder; when painting indoors, the warm-colored lithium slag powder is selected to prepare the gypsum paint.

[0039] Compared with the prior art, the gypsum coating which can utilize solid waste and is not easy to fall off and the preparation method thereof have the following beneficial effects:

[0040] In the present invention, lithium slag powder is used to replace talcum powder / light calcium powder, which not only realizes waste utilization and reduces the consumption of natural resources (traditional fillers such as talcum powder, light calcium, heavy calcium, etc. need to consume natural resources), but also due to the microstructure of lithium slag powder (large particle size distribution range, similar to the grading effect of concrete, and calcination causes it to contain glass microspheres), the filling performance of gypsum coating is improved, and it can be closely attached to the building base, thereby improving the adhesion of the coating, making it not easy to fall off and reducing the treatment requirements for the building base;

[0041] In the present invention, by adopting a method of mixing titanium dioxide and lithium slag powder of various whitenesses, it is ensured that the color of the lithium slag powder is uniform and the whiteness meets the construction requirements, so that the color of the gypsum coating is uniform and the problem of yellowing of the lithium slag powder is overcome, thereby avoiding the limitation of the use scenarios of the gypsum coating after the lithium slag powder is mixed into the gypsum coating. DETAILED DESCRIPTION

[0042] A gypsum coating that can utilize solid waste and is not easy to fall off, wherein the dry powder of the gypsum coating contains the following components in parts by weight:

[0043] 30-70 parts of gypsum powder;

[0044] 30-70 parts of filler powder; the filler powder is lithium slag powder whose whiteness is improved by adding titanium dioxide or lithium slag powder with higher whiteness, and the whiteness of the filler powder is not less than 55%;

[0045] Here, lithium slag powder with higher whiteness is preferred to improve whiteness, because this will not increase the cost. If lithium slag powder with higher whiteness is not available, white pigment must be added to improve whiteness. Among the white pigments that can be added, only titanium dioxide can improve whiteness a lot with a little addition, because it not only has a high whiteness and can improve the reflectivity of the surface of the object, but also has a strong covering effect. Other white pigments have poor covering effects, so a lot of them need to be added to increase the whiteness of lithium slag powder to the required value, which is not cost-effective.

[0046] Note that the whiteness in this application refers to the blue light whiteness, which can be quickly measured using a whiteness meter.

[0047] Whiteness of 55% is a threshold value. The surface of paint with whiteness of 55% is similar to darker newsprint, which can be covered by applying other paints on the surface. Such colored plaster paint can be used as a base coat. When the value is lower than this, the surface color of the plaster paint will appear obvious gray, which is difficult to cover with many topcoats. It is necessary to apply thick topcoat or use topcoat with strong covering power.

[0048] Note that the whiteness here refers to the whiteness of the gypsum paint dry powder or the solidified gypsum paint. The gypsum paint slurry usually has a very low whiteness and looks similar to cement mortar.

[0049] In addition to the above two main components, 0.4-1 parts of hydrophilic fiber powder need to be added here. Because in actual use, we found that the solidification process of gypsum paint mixed with lithium slag powder is faster than that of conventional gypsum paint, so a certain amount of fiber powder needs to be added to avoid cracking. Here, since the surface polarity of lithium slag powder is very strong and it has strong water absorption, it is necessary to use hydrophilic fiber powder to ensure that it is closely combined with lithium slag powder. The upper limit of 0.4-1 parts of this range is the upper limit of the amount to avoid the balling of hydrophilic fiber powder, and the lower limit is the lower limit of the amount to avoid cracking.

[0050] If the gypsum coating is a surface coating, the dry powder of the gypsum coating contains the following components in parts by weight:

[0051] 50-70 parts of gypsum powder; more gypsum powder is needed in the surface coating, which is a common practice and will not be repeated here;

[0052] 30-50 parts of filler powder; the whiteness of filler powder is 70-80%; the inner layer of paint is directly exposed to the outside, so it needs to be white enough; 70% is the lower limit of whiteness that can be accepted by the owner, if it is lower, it will be obviously gray, affecting the appearance; and 80% is a whiteness that can be achieved at a relatively low cost with the existing lithium slag powder, if it is higher, a lot of titanium dioxide needs to be added (because titanium dioxide has a significant effect on improving whiteness when the whiteness is lower), and the cost will increase significantly;

[0053] 0.4-1 part of hydrophilic fiber powder.

[0054] If the gypsum coating is the base coating, the dry powder of the gypsum coating contains the following components in parts by weight:

[0055] 30-50 parts of gypsum powder; more filler powder is needed in the base coating, which is a common practice and will not be repeated here;

[0056] 50-70 parts of filler powder; the whiteness of the filler powder is 55%-70%; since it is located under other coatings, it only needs to be covered;

[0057] 0.4-1 part of hydrophilic fiber powder.

[0058] The lithium slag powder in the filler powder is made by grinding the lithium slag produced by the calcination and lithium extraction process. Such lithium slag powder contains glass microspheres with a wide range of particle size distribution, which has the effect of enhancing the adhesion of the paint. This effect is an unexpected gain. In the experiment, it was found that its adhesion is stronger than that of the existing gypsum paint, and then subsequent research discovered the mechanism of strong adhesion.

[0059] The mesh number of lithium slag powder in the filler powder is not less than 400 meshes, and is higher than the mesh numbers of gypsum powder and titanium dioxide. In actual use, this value can easily reach 800 meshes, so that it can be filled into the gaps between gypsum powder and titanium dioxide, playing a similar role to the coarse and fine aggregate grading in concrete, further improving the strength of the gypsum paint after solidification. If the mesh number of lithium slag powder is high, the dust it stirs up during mixing will be very obvious, and it is easy to stratify with titanium dioxide during transportation due to density reasons. Therefore, it is best to pack the prepared paint dry powder in an inner packaging bag made of soluble film, and then put on a vacuum packaging bag and evacuate it, so that the paint dry powder will not be drawn into it during vacuuming. After vacuuming, it will be a hard block, will not be stratified during transportation, and will not be affected by moisture. At the same time, there is no need to remove the soluble film when mixing. The whole bag can be directly put into the mixer and covered with a lid, and there will be no dust at all.

[0060] The hydrophilic fiber powder is wood fiber powder or waste paper fiber powder. The hydrophilic fiber powder is also doped with sodium carboxymethyl cellulose for further improving the bonding strength between the hydrophilic fiber powder and the rest of the gypsum coating. The content of sodium carboxymethyl cellulose in the hydrophilic fiber powder is 6%-10%wt. This range can ensure that the surface of the hydrophilic fiber powder is fully covered with sodium carboxymethyl cellulose. The reason why wood fiber powder or waste paper fiber powder is used here is that these two ingredients can be made from the leftovers in the forestry production process or recycled waste paper, that is, they can utilize some other types of solid waste. At the same time, sodium carboxymethyl cellulose can further increase the viscosity of the coating slurry to prevent the high-density titanium dioxide and low-density lithium slag powder from stratifying after the slurry is left to stand.

[0061] A method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off is used to prepare the above-mentioned gypsum coating that can utilize solid waste and is not easy to fall off, and comprises the following steps:

[0062] Step 1: Take 100 parts by mass of lithium slag powder with a whiteness of no more than 55%, add titanium dioxide gradually by mass, flatten and compact the lithium slag powder and measure the whiteness of the lithium slag powder once each time 1 part by mass of titanium dioxide is added and mixed, until the whiteness of the lithium slag powder is higher than 80%; then draw a whiteness-titanium dioxide addition amount curve; in the whiteness-titanium dioxide addition amount curve, the ordinate is the whiteness of the lithium slag powder after adding titanium dioxide, and the abscissa is the mass fraction of titanium dioxide added.

[0063] The reason why the lithium slag powder is flattened and compacted here is to avoid the powder affecting the measurement results (under certain lighting angles, unflattened and compacted powder may be brighter or darker than the actual situation). The reason why the color of the adjusted lithium slag powder is measured instead of the effect after the gypsum paint is applied is to save time and workload. Because the whiteness of the lithium slag powder is controlled in order to make the whiteness of the gypsum paint meet the standard. In actual use, it is found that as long as the whiteness of the flattened and compacted lithium slag powder meets the standard, then the whiteness after mixing it into gypsum paint and brushing it can meet the standard, and there is no need to go through the subsequent mixing, painting, and curing process.

[0064] If you need to get the result quickly, you can also use this method: 1000 parts by mass of titanium dioxide is divided into 10 piles, and 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, 10, and 20 parts by mass of titanium dioxide are added into them respectively, mixed well, and the whiteness of 10 piles of titanium dioxide is measured at one time, and then the curve is drawn. Although the color of the actual lithium slag powder is obviously different, it can generally be adjusted to the required color within the doping range of this titanium dioxide.

[0065] In this embodiment, 12 parts by mass of titanium dioxide are added to 100 parts by mass of lithium slag powder to obtain lithium slag powder with a whiteness of 80%, thereby obtaining a filler.

[0066] Step 2: Stock up multiple batches of lithium slag powder in the warehouse. Each batch of lithium slag powder corresponds to a color. Measure the whiteness of each batch of lithium slag powder in the warehouse and record it; thereby providing a basis for the subsequent preparation process.

[0067] Step 3: The whiteness of the filler powder required in the construction design stage is recorded as B;

[0068] If there is lithium slag powder with a whiteness greater than B in the warehouse, filler powder is prepared by mixing two types of lithium slag powder with a whiteness greater than B and less than B;

[0069] Generally, it is not the case that the whiteness of all lithium slag powder in the warehouse is higher than the demand. If there is, it can be used directly without further adjustment. The reason why lithium slag powder with a whiteness greater than B is not used directly but mixed with other lithium slag powders is that there is less lithium slag powder with a higher whiteness.

[0070] If there is no lithium slag powder with a whiteness greater than B in the warehouse, filler powder is prepared by adding titanium dioxide to the lithium slag powder with a whiteness less than B; the whiteness of titanium dioxide is the highest among common white substances, and its whiteness must be higher than B, so it can be used to improve the whiteness of the darker lithium slag powder.

[0071] Step 4: After mixing the gypsum powder, filler powder and hydrophilic fiber powder, add water and mix to obtain the finished gypsum paint.

[0072] In step 3, two lithium slag powders with whiteness greater than B and less than B are mixed to prepare filler powder in the following manner:

[0073] Select two lithium slag powders with whiteness closest to B and one greater than B and the other less than B, the whiteness of the lithium slag powder greater than B is recorded as A, and the whiteness of the lithium slag powder less than B is recorded as C, then every 100 weight parts of filler powder contains 100 (BC) / (AC) parts by weight of lithium slag powder with whiteness greater than A, and 100 (AB) / (AC) parts by weight of lithium slag powder with whiteness less than A;

[0074] Here, the process of using whiter lithium slag powder to improve whiteness is a process of mixing the same substances, and there is no covering effect (because the refractive index is the same). If the same substances are mixed, the whiteness is completely linearly related to the proportion of each component (whiteness A and whiteness C have no mutual covering effect on the coating surface and can be regarded as independent of each other), so the interpolation method can be used for preparation.

[0075] In step 3, titanium dioxide is added to lithium slag powder having a whiteness less than B to prepare filler powder in the following manner:

[0076] Select a lithium slag powder with the whiteness closest to B, and record its whiteness as D;

[0077] The horizontal lines with vertical coordinates B and D intersect the whiteness-titanium dioxide addition amount curve, and the horizontal coordinate difference between the two intersection points is recorded as U. Then, the required filler powder can be obtained by adding U parts by mass of titanium dioxide to every 100 parts by mass of lithium slag powder with a whiteness of D.

[0078] Here, since titanium dioxide has a covering effect on lithium slag powder, the functional relationship between its added amount and the whiteness of lithium slag powder is nonlinear. Here, the doping amount is obtained by fitting the experimental data curve.

[0079] In step 2, the whiteness of the lithium slag powder is recorded while the CMYK color of the lithium slag powder is recorded, wherein the lithium slag powder with a warm CMYK color is recorded as warm-colored lithium slag powder; when painting indoors, warm-colored lithium slag powder is selected to prepare gypsum paint.

[0080] This application conducted a control experiment, as follows:

[0081] Experimental group: 50 parts by weight of gypsum powder; 50 parts by weight of filler powder, obtained by adding 12 parts by weight of titanium dioxide to 100 parts by weight of lithium slag powder; 1 part by weight of hydrophilic fiber powder, which is wood fiber powder containing 10%wt of sodium carboxymethyl cellulose;

[0082] Control group: Replace the filler in the experimental group with talcum powder;

[0083] The experimental group and the control group were respectively prepared into coating slurries, which were applied on the unroughened and dusty concrete walls, and the adhesion conditions were observed after solidification.

[0084] Experimental results: The paint in the control group fell off, but not in the experimental group. There was no significant difference in color after solidification (under indoor, daytime, natural light).

[0085] The embodiments described above are merely descriptions of preferred implementation modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off, characterized in that: Used to prepare gypsum coating, the dry powder of gypsum coating contains the following components by weight: 30-70 parts of gypsum powder; 30-70 parts of filler powder; the filler powder is lithium slag powder whose whiteness is improved by adding titanium dioxide or lithium slag powder with higher whiteness, and the whiteness of the filler powder is not less than 55%; 0.4-1 part of hydrophilic fiber powder; The preparation method comprises the following steps: Step 1: Take 100 parts by mass of lithium slag powder with a whiteness of no more than 55%, add titanium dioxide in portions by mass, flatten and compact the lithium slag powder and measure the whiteness of the lithium slag powder once after adding 1 part by mass of titanium dioxide and mixing, until the whiteness of the lithium slag powder is higher than 80%; then draw a whiteness-titanium dioxide addition amount curve; in the whiteness-titanium dioxide addition amount curve, the ordinate is the whiteness of the lithium slag powder after adding titanium dioxide, and the abscissa is the mass fraction of titanium dioxide added; Step 2: Stock up multiple batches of lithium slag powder in the warehouse, each batch of lithium slag powder corresponds to a color, measure the whiteness of each batch of lithium slag powder in the warehouse and record it; Step 3: The whiteness of the filler powder required in the construction design stage is recorded as B; If there is lithium slag powder with a whiteness greater than B in the warehouse, filler powder is prepared by mixing two types of lithium slag powder with a whiteness greater than B and less than B; If there is no lithium slag powder with a whiteness greater than B in the warehouse, filler powder is prepared by adding titanium dioxide to lithium slag powder with a whiteness less than B; Step 4: After mixing the gypsum powder, filler powder and hydrophilic fiber powder, the dry paint powder is packed in an inner packaging bag made of a soluble film, and then covered with a vacuum packaging bag and vacuumed; When mixing, the soluble film is not removed, and the whole package is directly put into the mixer, then the lid is closed, and water is added to mix to obtain the finished gypsum paint.

2. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: The gypsum coating is a surface coating, and the dry powder of the gypsum coating contains the following components in parts by weight: 50-70 parts of gypsum powder; 30-50 parts of filler powder; the whiteness of the filler powder is 70-80%; 0.4-1 part of hydrophilic fiber powder.

3. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: The gypsum coating is a primer, and the dry powder of the gypsum coating contains the following components in parts by weight: 30-50 parts of gypsum powder; 50-70 parts of filler powder; the whiteness of the filler powder is 55%-70%; 0.4-1 part of hydrophilic fiber powder.

4. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: The lithium slag powder in the filler powder is obtained by grinding lithium slag produced by a calcination lithium extraction process.

5. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 4, characterized in that: The mesh size of the lithium slag powder in the filler powder is not less than 400 meshes, and is higher than the mesh sizes of the gypsum powder and the titanium dioxide.

6. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: The hydrophilic fiber powder is wood fiber powder or waste paper fiber powder. The hydrophilic fiber powder is also doped with sodium carboxymethyl cellulose for further improving the bonding strength between the hydrophilic fiber powder and the rest of the gypsum coating. The content of sodium carboxymethyl cellulose in the hydrophilic fiber powder is 6%-10%wt.

7. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: In step 3, two lithium slag powders with whiteness greater than B and less than B are mixed to prepare filler powder in the following manner: Select two lithium slag powders whose whiteness is closest to B and one is greater than B and the other is less than B. The whiteness of the lithium slag powder with a whiteness greater than B is recorded as A, and the whiteness of the lithium slag powder with a whiteness less than B is recorded as C. Then, every 100 parts by weight of filler powder contains 100 (BC) / (AC) parts by weight of lithium slag powder with a whiteness greater than A and 100 (AB) / (AC) parts by weight of lithium slag powder with a whiteness less than A.

8. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: In step 3, titanium dioxide is added to lithium slag powder having a whiteness less than B to prepare filler powder in the following manner: Select a lithium slag powder with the whiteness closest to B, and record its whiteness as D; The horizontal lines with vertical coordinates B and D intersect the whiteness-titanium dioxide addition amount curve, and the horizontal coordinate difference between the two intersection points is recorded as U. Then, the required filler powder can be obtained by adding U parts by mass of titanium dioxide to every 100 parts by mass of lithium slag powder with a whiteness of D.

9. The method for preparing a gypsum coating that can utilize solid waste and is not easy to fall off according to claim 1, characterized in that: In step 2, the whiteness of the lithium slag powder is recorded while the CMYK color of the lithium slag powder is recorded, wherein the lithium slag powder with a warm CMYK color is recorded as warm-colored lithium slag powder; when painting indoors, warm-colored lithium slag powder is selected to prepare gypsum paint.

Citation Information

Patent Citations

  • Method for producing white dry powder building coating base stock

    CN103030348A

  • Production method of dry-mixed facing mortar with controllable whiteness

    CN103043966A

  • Lithium silicon powder used as gypsum reinforcing agent and plastering gypsum containing same

    CN1345701A